Protective effects of diallyl disulfide against acetaminophen-induced nephrotoxicity: A possible role of CYP2E1 and NF-κB. (April 2017) - Ko, Je-Won; Shin, Jin-Young; Kim, Jeong-Won; Park, Sung-Hyeuk; Shin, Na-Rae; Lee, In-Chul; Shin, In-Sik; Moon, Changjong; Kim, Sung-Ho; Kim, Sung-Hwan; Kim, Jong-Choon
Abstract: Diallyl disulfide (DADS) is a degradation product of allicin which is contained in garlic. This study investigated the protective effects of DADS against acetaminophen (AAP)-induced nephrotoxicity and the molecular mechanisms of nephroprotective effects in rats. AAP caused severe nephrotoxicity as evidenced by significant increases in renal tubular cell apoptosis, mitochondria-mediated apoptosis, and up-regulation of nuclear transcription factor kappa-B (NF-κB), cyclooxygenase-2 (Cox-2), and tumor necrosis factor-α (TNF-α) in the kidney with histopathological alterations. After AAP administration, glutathione content and activities of catalase, superoxide dismutase, and glutathione reductase were significantly decreased whereas malondialdehyde content was significantly increased, indicating that AAP-induced kidney injury was mediated through oxidative stress. In contrast, DADS pretreatment significantly attenuated AAP-induced nephrotoxic effects, including oxidative damage, histopathological lesions, and apoptotic changes in the kidney. DADS also attenuated AAP-induced up-regulation of NF-κB, Cox-2, and TNF-α in the kidney, and microsomal CYP2E1 expression in liver and kidney. These results indicated that DADS could prevent AAP-induced nephrotoxicity. The protective effects of DADS might be due to its ability to decrease metabolic activation of AAP by inhibiting CYP2E1 and its potent antioxidant, antiapoptotic, and antiinflammatory effects via inhibition of NF-κB. Highlights: Nephroprotective effects of diallyl disulfide (DADS) were investigated. DADS protected oxidative nephrotoxicity induced by acetaminophen (AAP). DADS suppressed metabolic activation of AAP by suppressing CYP2E1 expression. DADS showed antioxidant, antiapoptotic, and antiinflammatory effects via inhibition of NF-κB.